Mesenchymal Stromal Cells Promote Retinal Vascular Repair by Modulating Sema3E and IL-17A in a Model of Ischemic Retinopathy - Noueihed, Baraa; Rivera, José Carlos; Dabouz, Rabah; Abram, Pénélope; Omri, Samy; Lahaie, Isabelle; Chemtob, Sylvain (Frontiers in Cell and Developmental Biology, 2021)
Ischemic retinopathies (IRs), such as retinopathy of prematurity and diabetic retinopathy, are characterized by an initial phase of microvascular degeneration that results in retinal ischemia, followed by exaggerated pathologic neovascularization (NV). Mesenchymal stromal cells (MSCs) have potent pro-angiogenic and anti-inflammatory properties associated with tissue repair and regeneration, and in this regard exert protection to neurons in ischemic and degenerative conditions; however, the exact mechanisms underlying these functions remain largely unknown. Class III Semaphorins (A-G) are particularly implicated in regulating neural blood supply (as well as neurogenesis) by suppressing angiogenesis and affecting myeloid cell function; this is the case for distinct neuropillin-activating Sema3A as well as PlexinD1-activating Sema3E; but during IR the former Sema3A increases while Sema3E decreases. We investigated whether retinal vascular repair actions of MSCs are exerted by normalizing Semaphorin and downstream cytokines in IR. Intravitreal administration of MSCs or their secretome (MSCs-conditioned media [MSCs-CM]) significantly curtailed vasoobliteration as well as aberrant preretinal NV in a model of oxygen-induced retinopathy (OIR). The vascular repair effects of MSCs-CM in the ischemic retina were associated with restored levels of Sema3E. Vascular benefits of MSCs-CM were reversed by anti-Sema3E; while intravitreal injection of anti-angiogenic recombinant Sema3E (rSema3E) in OIR-subjected mice reproduced effects of MSCs-CM by inhibiting as expected preretinal NV but also by decreasing vasoobliteration. To explain these opposing vascular effects of Sema3E we found in OIR high retinal levels respectively of the pro- and anti-angiogenic IL-17A and Sema3A-regulating IL-1; IL-17A positively affected expression of IL-1. rSema3E decreased concentrations of these myeloid cell-derived pro-inflammatory cytokines in vitro and in vivo. Importantly, IL-17A suppression by MSCs-CM was abrogated by anti-Sema3E neutralizing antibody. Collectively, our findings provide novel evidence by which MSCs inhibit aberrant neovascularization and diminish vasoobliteration (promoting revascularization) in retinopathy by restoring (at least in part) neuronal Sema3E levels that reduce pathological levels of IL-17A (and in turn other proinflammatory factors) in myeloid cells. The ability of MSCs to generate a microenvironment permissive for vascular regeneration by controlling the production of neuronal factors involved in immunomodulatory activities is a promising opportunity for stem cell therapy in ocular degenerative diseases.